The changing structure of red meat demand - James Mintert (Kansas Agricultural Experiment Station Research Reports, 1987)
Testing for a demand change was done using pork and beef demand models estimated over the 1950-1984 period. Results suggest that a structural change has taken place in both beef and pork demand. The beef demand change, however, appears to have been more severe than that noted for pork.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Red Meat; Demand